Third Five-Year Plan Annual Plan 1965-66 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1965)
Agricultural Production, Training Centres, Land Development, Consolidation of Holdings, Development of Ayacuts, Minor Irrigation, Soil Conservation, Animal Husbandry, Dairying and Milk Supply, Forests, Fisheries, Warehousing and Marketing, Co-operation, Community Development Programme, Nagarjunasagar Multi-purpose Project, Major and Medium Irrigation including Flood Control, Power, Large and Medium Industries, Mineral Development, Village and Small Scale Industries, Handlooms.
Planning Department, Government of Andhra Pradesh